2021
DOI: 10.1021/acsami.1c01734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TiN Top Electrode Texturing on Ferroelectricity in Hf1–xZrxO2

Abstract: Ferroelectric memories based on hafnium oxide are an attractive alternative to conventional memory technologies due to their scalability and energy efficiency. However, there are still many open questions regarding the optimal material stack and processing conditions for reliable device performance. Here, we report on the impact of the sputtering process conditions of the commonly used TiN top electrode on the ferroelectric properties of Hf 1– x Zr x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…[356] In contrast, they assumed oxide electrodes to be transparent to the migration of oxygen vacancies; the fatigue effect in this kind of capacitor is therefore very small. [356] Recently, Athle et al [359] found that the P r of Zr-doped HfO 2 thin films is substantially affected by the texturing of the TiN film as a top electrode, ranging from almost zero for the majority (002) texture up to 30 µC cm -2 for the majority (111) texture.…”
Section: Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…[356] In contrast, they assumed oxide electrodes to be transparent to the migration of oxygen vacancies; the fatigue effect in this kind of capacitor is therefore very small. [356] Recently, Athle et al [359] found that the P r of Zr-doped HfO 2 thin films is substantially affected by the texturing of the TiN film as a top electrode, ranging from almost zero for the majority (002) texture up to 30 µC cm -2 for the majority (111) texture.…”
Section: Electrodesmentioning
confidence: 99%
“…Recently, Athle et al [ 359 ] found that the P r of Zr‐doped HfO 2 thin films is substantially affected by the texturing of the TiN film as a top electrode, ranging from almost zero for the majority (002) texture up to 30 µC cm −2 for the majority (111) texture.…”
Section: Parameters Influencing the Ferroelectric Propertiesmentioning
confidence: 99%
“…The simulated peak surface temperatures of 550-710 °C are in the upper range and above the usually reported crystallization temperature of 400-600 °C required to form the ferroelectric orthorhombic phase in HZO. [2,11,[27][28][29] Thus, utilizing pulse energies in the range of 20-30 J cm -2 should yield a sufficiently high peak temperature to achieve ferroelectric properties in the HZO.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Ferroelectric HfO 2 is typically achieved by crystallization of an amorphous thin film into the non-centrosymmetric orthorhombic phase Pca2 1 , which can be stabilized by doping and appropriate tensile stress from a metal electrode. [9,10] A common practice to achieve the orthorhombic phase is to form an alloy of HfO 2 with Zr, a popular choice due to the stability in the alloy composition. [11] To induce crystallization, a rapid thermal process (RTP) is usually performed in the range of 400-1000 °C for tens of seconds up to minutes.…”
mentioning
confidence: 99%
“…Recently, Athle et al reported that the ferroelectric properties of HZO films could be dependent on the TiN TE texture [40]. Their 111-textured TiN TE sample exhibited a high polarization value.…”
Section: Resultsmentioning
confidence: 99%